What if the future of HER2‐positive breast cancer patients was written in miRNAs? An exploratory analysis from NeoALTTO study. (17th December 2021) - Pizzamiglio, Sara; Cosentino, Giulia; Ciniselli, Chiara M.; De Cecco, Loris; Cataldo, Alessandra; Plantamura, Ilaria; Triulzi, Tiziana; El‐abed, Sarra; Wang, Yingbo; Bajji, Mohammed; Nuciforo, Paolo; Huober, Jens; et al.
Abstract: Background: Neoadjuvant therapy with dual HER2 blockade improved pathological complete response (pCR) rate in HER2‐positive breast cancer patients. Nevertheless, it would be desirable to identify patients exquisitely responsive to single agent trastuzumab to minimize or avoid overtreatment. Herein, we evaluated the predictive and prognostic value of basal primary tumor miRNA expression profile within the trastuzumab arm of NeoALTTO study (ClinicalTrials.gov Identifier: NCT00553358 ). Methods: RNA samples from baseline biopsies were randomized into training ( n = 45) and testing ( n = 47) sets. After normalization, miRNAs associated with Event‐free survival (EFS) and pCR were identified by univariate analysis. Multivariate models were implemented to generate specific signatures which were first confirmed, and then analyzed together with other clinical and pathological variables. Results: We identified a prognostic signature including hsa‐miR‐153‐3p (HR 1.831, 95% CI: 1.34–2.50) and hsa ‐ miR ‐ 219a ‐ 5p (HR 0.629, 95% CI: 0.50–0.78). For two additional miRNAs ( miR‐215‐5p and miR‐30c‐2‐3p ), we found a statistically significant interaction term with pCR (p.interaction: 0.017 and 0.038, respectively). Besides, a two‐miRNA signature was predictive of pCR ( hsa‐miR‐31‐3p, OR 0.70, 95% CI: 0.53–0.92, and hsa‐miR‐382‐3p, OR: 1.39, 95% CI: 1.01–1.91). Notably, the performance of this predictive miRNA signature resembled that of the genomic classifiers PAM50 and TRAR, and did not improve when the extended models were fitted. Conclusion: Analyses of primary tumor tissue miRNAs hold the potential of a parsimonious tool to identify patients with differential clinical outcomes after trastuzumab based neoadjuvant therapy. Abstract : Despite the improved pathological complete response rate in HER2‐positive breast cancer patients with neoadjuvant dual HER2 blockade, it would be desirable to identify patients exquisitely responsive to single agent trastuzumab to minimize or avoid overtreatment. Herein, by analyzing baseline tissue microRNA (miRNA) profile in the trastuzumab arm of NeoALTTO study, we identified a two‐miRNA predictive signature and a prognostic signature associated to event‐free survival. Analyses of primary tumor tissue miRNAs hold the potential of a parsimonious tool to identify patients with differential clinical outcomes after trastuzumab based neoadjuvant therapy.